Investigation of the pedaling forces in a cycling field test using the non-linear measure ML1 - Kunert, A.; Koska, D.; Maiwald, C. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2021)
The study of biomechanical and physiological variables allows human movement scientists to investigate the characteristics of movement patterns in cyclists. While straightforward and well-investigated, linear measures may not adequately capture the underlying complexity of movements during cycling. Therefore, a non-linear phase-space measure (ML1) was applied to forces and heart rates of nine cyclists in a field test. The test was repeated two times with different instructions on how to alter the bike`s gearing while cycling a 12.5 km long level track. Pedaling forces and heart rates were measured. Future aim of the underlying study is the investigation of innovative control algorithms for e-bike propulsions. Force-time curves were sequenced into single cycles, linearly interpolated in the time domain, and z-score normalized. ML1 was calculated in a flowing window algorithm of 50 cycles. With fixed gearing, a contrast analysis showed that changes in terrain inclination were strongly associated with changes in the non-linear measure ML1. The calculation of Spearman`s cross correlation showed high coefficients of correlation between ML1 and delayed heart rate. The results indicate systematic changes of the pedaling movement as an adaptive response to changes in terrain inclination. Future research may utilize the findings from this study to investigate possible relationships between subjective measures of exhaustion, comfort, and discomfort with biomechanical characteristics of the pedaling movement.